Polymerization of ethylene to branched poly(ethylene)s using ansa-eta(5)-monofluorenyl cyclohexanolato zirconium(IV) complex/methylaluminoxane - Rajesh, A.; Sivaram, S. (Polymer Bulletin, 2011)
ansa-eta(5)-Monofluorenyl cyclohexanolato zirconium complex 3 was shown to be active for the polymerization of ethylene when activated with methylaluminoxane (MAO) at 5 bar. Up to a polymerization temperature of 40 A degrees C, 3/MAO resulted in linear poly(ethylene)s with saturated chain ends. However, at polymerization temperatures of 60, 80, and 100 A degrees C, a mixture of branched poly(ethylene)s, linear alpha-olefins and long chain alkanes was obtained. The poly(ethylene)s produced at 80 and 100 A degrees C exhibited a bimodal molecular weight distribution indicative of multiple active species. Very high molecular weight (M (v) > 5 x 10(5)) linear poly(ethylene)s were obtained using 3/MAO at 25 A degrees C.
Keywords: ansa-Monofluorenyl complex; Bimodal MWD; Branched poly(ethylene)s; Ethylene polymerization; Methyl aluminoxane